PKU bagi MI Muhammadiyah Madukoro dan Wonogiri Kabupaten Magelang melalui Implementasi Standar Nasional Pendidikan Dasar dalam Pengembangan Mutu Madrasah - Oktradiksa, Ahwy -; Sari, Kanthi Pamungkas; Shalikhah, Norma Dewi (WARTA, 2018)
The issues facing the Madrasah Ibtidaiyah Muhammadiyah Madukoro and Magelang Regency Wonogiri is a low level of understanding of knowledge about SNP, inequalities in educational development, objective conditions of teachers and resources involved have the ability of low, low management capabilities of the madrasa, lack the support of stakeholders in the development of the madrasa. The purpose of the research is accomplishing the implementation system national standards of education through madrasah quality development with the learning media design is good. The methods used are participatory empowerment model i.e. Participatory Rural Appraisal (PRA). The results of the devotion to the development of quality learning through the medium of the madrassa showed good results because of the understanding of national standards of education in madrasah is in need of mentoring that is accurate in order to realize a superior madrasah and produce competent graduates through teaching with creative learning media.